Pengembangan Media Pembelajaran Interaktif Materi Sistem Pencernaan Manusia Berbasis Macromedia Flash - Hasibuan, Adek Indah Aryati; Khairuddin, Khairuddin; Khairuna, Khairuna (Jurnal Simki Pedagogia, 2023)
This study aims to determine the development and feasibility of interactive learning media based on macromedia flash on the material of the human digestive system. This study uses the ADDIE development model (Analysis, Design, Development, Implement, and Evaluation). This research was carried out in January 2022 with a research sample of 34 students in class XI MIA-1 MAN Pematangsiantar. The result of the research is to produce an interactive learning media product based on macromedia flash which is developed to contain material on the human digestive system. To test the feasibility of macromedia flash-based interactive learning media by validating the products made to the material expert team, the average percentage score was 84%, by media experts, 91%, by Biology teachers (field practitioners) 85% and by students 86%. So that it can be concluded that the interactive learning media based on macromedia flash is feasible to use in the biology learning process on the material of the human digestive system.